Formal notes on Coeur d'Alene clause structure - Bischoff, Shannon T. (Cambridge Scholars Publishing, 2010)
Coeur d'Alene, also known as Snchitsu'umshtsn, is a Southern Interior (Idaho, USA) Salish language. This work presents a formal account of the basic clause structure of this polysynthetic language within the tradition of Minimalism and Distributed Morphology. The work arrives at an account of the basic clause structure and an articulation of the left periphery of Coeur d'Alene. In addition, an account of lexical affixation is presented. Thus providing the first formal account of the language ...